Jombang district community perceptions of women trainers - abdul jabbar albaihaqi; Kurniati Rahayuni; Prisca Widiawati (Universitas Riau, 2024)
(English)This reseacrh aims to determine the perception of people in Jombang Regency towards female trainers. ‎This research is motivated by: 1) negative perception and patriarchal culture, where sport is ‎considered only for men and women are considered incapable of success in the field of sport 2) the ‎coaching profession in Indonesia has always been dominated by men, which indicates limited access ‎for women to have coaching experience; 3) social assumptions that lead to discrimination against ‎women who engage in sports activities. This reseacrh used a descriptive quantitative approach, the ‎participants of the reseacrh were the people of Jombang Regency totalling 104 men and 107 women, who ‎used sports infrastructure, could read and write and were adults. This research was conducted by using questionnaires as the validated and disseminated through googleform and pasted information on notice boards in ‎sports venues. This research analysis technique is using descriptive statistics, such as frequency, mean, ‎median, and standard deviation can be used to analyse respondent characteristics, such as age, gender, ‎education level, and level of involvement in sports. The results of this study can be known that 1) ‎external internal barriers, many female trainers often experience fatigue. 2) organizational barriers, ‎government support is still lacking for female trainers. 3) Socio-cultural barriers, the profession of ‎female trainer is a profession that is widely demanded by society to produce achievements. 4) Gender ‎barriers, coach recruitment systems favour men over women. (Indonesian)Penelitian ini bertujuan untuk mengetahui persepsi masyarakat di Kabupaten ‎Jombang terhadap ‎‎pelatih Perempuan. Penelitian ini dilatarbelakangi oleh: 1) ‎persepsi buruk dan budaya patriarki, yaitu ‎dimana olahraga dianggap hanya untuk laki-laki saja dan perempuan dianggap tidak mampu sukses di ‎bidang olahraga 2) ‎profesi pelatih di Indonesia selalu ‎didominasi oleh laki-laki, yang mengidikasikan ‎terbatasnya akses untuk perempuan untuk memiliki pengalaman melatih; 3) Anggapan sosial yang ‎mengarah pada ‎diskriminasi ‎terhadap perempuan yang melakukan aktifitas olahraga, dimana ‎perempuan dianggap lemah dan tidak mampu berolahraga sebaik laki-laki. Penelitian ini menggunakan ‎‎‎pendekatam kuantitatif deskriptif, Partisipan penelitian adalah masyarakat ‎Kabupaten Jombang yang ‎‎berjumlah 104 orang laki-laki dan 107 orang perempuan, ‎yang menggunakan sarana prasarana ‎‎olahraga, bisa baca tulis dan usia dewasa. ‎Penelitian ini menggunakan kuesioner yang sudah ‎‎divalidasi dan ‎menyebarkan melalui googleform dan menempelkan informasi di papan ‎pengumuman ‎‎di tempat-tempat olahraga. Teknik analisis penelitian ini adalah ‎mengunakan statistik deskripif, seperti ‎‎frekuensi, mean, median, dan standar deviasi ‎dapat digunakan untuk menganalisis karakteristik ‎‎responden, seperti usia, jenis ‎kelamin, tingkat pendidikan, dan tingkat keterlibatan dalam olahraga. ‎‎Hasil ‎penelitian ini dapat diketahui bahwa 1) hambatan internal eksternal, banyak pelatih ‎perempuan ‎‎sering mengalami kelelahan. 2) hambatan organisasi,dukungan ‎pemerintah masih kurang terhadap ‎‎pelatih perempuan. 3) hambatan sosial budaya, ‎profesi pelatih perempuan adalah profesi yang banyak ‎‎di tuntut oleh masyarakat ‎untutk menghasilkan prestasi. 4) hambatan gender, sistem perekrutan ‎‎pelatih lebih ‎menguntungkan laki-laki daripada perempuan.‎Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.